2017
DOI: 10.1007/978-3-319-62127-2_30
|View full text |Cite
|
Sign up to set email alerts
|

Improved Distance Sensitivity Oracles via Tree Partitioning

Abstract: We introduce an improved structure of distance sensitivity oracle (DSO). The task is to pre-process a non-negatively weighted graph so that a data structure can quickly answer replacement path length for every triple of source, terminal and failed vertex. The previous best algorithm constructs in time 1Õ (mn) a distance sensitivity oracle of size O(n 2 log n) that processes queries in O(1) time. As an improvement, our oracle takes up O(n 2 ) space, while preserving O(1) query efficiency andÕ(mn) preprocessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A natural data structure analog of fault-tolerant subgraphs are distance sensitivity oracles, which are small data structure that are used to answer queries of the form: "what is the distance between s and t in G when a set of F edges fail"? There is a long line of literature on constructing distance sensitivity oracles [23,8,9,30,7,49,26,12] and related structures such a fault tolerant routing schemes [29,19] and labeling schemes [2]. Recently, [20] provided an efficient construction of distance sensitivity oracles that support f = O(log n/ log log n) many faults with polylogarithmic query time.…”
Section: Introductionmentioning
confidence: 99%
“…A natural data structure analog of fault-tolerant subgraphs are distance sensitivity oracles, which are small data structure that are used to answer queries of the form: "what is the distance between s and t in G when a set of F edges fail"? There is a long line of literature on constructing distance sensitivity oracles [23,8,9,30,7,49,26,12] and related structures such a fault tolerant routing schemes [29,19] and labeling schemes [2]. Recently, [20] provided an efficient construction of distance sensitivity oracles that support f = O(log n/ log log n) many faults with polylogarithmic query time.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the Õ(mn) time bound of [BK09] is optimal. Duan and Zhang [DZ17] improved the space complexity of the DSO to O(n 2 ), eliminating the last log n factor, while preserving constant query time and Õ(mn) preprocessing time.…”
Section: Related Workmentioning
confidence: 99%
“…They showed that it is possible to preprocess a directed weighted graph in O(mn 2 ) time to compute a data-structure of size O(n 2 log n) capable of answering distance queries in constant time. Bernstein and Karger [8] improved the preprocessing time to O(mn) and Duan and Zhang [23] reduced the space to O(n 2 ), which is asymptotically optimal.…”
Section: Related Workmentioning
confidence: 99%